Modulation of plant and bacterial polyamine metabolism during the compatible interaction between tomato and Pseudomonas syringae - Vilas, Juan Manuel (2018)
The polyamines putrescine, spermidine and spermine participate in a variety of cellular processes in all organisms. Many studies have shown that these polycations are important for plant immunity, as well as for the virulence of diverse fungal phytopathogens. However, the polyamines’ roles in the pathogenesis of phytopathogenic bacteria have not been thoroughly elucidated to date. To obtain more information on this topic, we assessed the changes in polyamine homeostasis during the infection of tomato plants by Pseudomonas syringae. Our results showed that polyamine biosynthesis and catabolism are activated in both tomato and bacteria during the pathogenic interaction. This activation results in the accumulation of putrescine in whole leaf tissues, as well as in the apoplastic fluids, which is explained by the induction of its synthesis in plant cells and also on the basis of its excretion by bacteria. We showed that the excretion of this polyamine by P. syringae is stimulated under virulence-inducing conditions, suggesting that it plays a role in plant colonization. However, no activation of bacterial virulence traits or induction of plant invasion was observed after the exogenous addition of putrescine. In addition, no connection was found between this polyamine and plant defence responses. Although further research is warranted to unravel the biological functions of these molecules during plant-bacterial interactions, this study contributes to a better understanding of the changes associated with the homeostasis of polyamines during plant pathogenesis.